2019
DOI: 10.1093/omcr/omz042
|View full text |Cite
|
Sign up to set email alerts
|

Reperfusion therapy of acute ischemic stroke in an all-in-one resuscitation room called a hybrid emergency room

Abstract: Acute ischemic stroke (AIS) caused by major vessel occlusion has potentially poor outcomes. Early successful recanalization after symptom onset is an important factor for favorable outcomes of AIS. We present the case of a 74-year-old man with AIS who underwent the entire process from diagnosis to thrombolysis and endovascular treatment in a hybrid emergency room (ER) equipped with a multidetector computed tomography (CT) scanner and an angiography suite set-up. A hybrid ER can facilitate evaluation and defini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Kinoshita et al was the first to report on the effectiveness of the installation of a hybrid ER in the trauma resuscitation on clinical outcomes and prognosis achieved the innovative trauma workflow. 10 In their historical controlled study, time to initiation of CT (Conventional group 26 [21][22][23][24][25][26][27][28][29][30][31][32] vs. hybrid ER 11 [8][9][10][11][12][13][14][15][16] min; p < 0.0001) and an emergency procedure (68 [51-85] vs. 47 [37-57] min; p < 0.0001) were both shorter in the hybrid ER group. A significant association was found between the hybrid ER and decreased mortality (adjusted odds ratio [aOR], 0.50; 95% confidence interval [CI], 0.29-0.85; p = 0.011) and reduced deaths from exsanguination (aOR, 0.17; 95% CI, 0.06-0.47; p = 0.001).…”
Section: Clinical Experience With Severe Trauma In the Hybrid Ermentioning
confidence: 98%
See 2 more Smart Citations
“…Kinoshita et al was the first to report on the effectiveness of the installation of a hybrid ER in the trauma resuscitation on clinical outcomes and prognosis achieved the innovative trauma workflow. 10 In their historical controlled study, time to initiation of CT (Conventional group 26 [21][22][23][24][25][26][27][28][29][30][31][32] vs. hybrid ER 11 [8][9][10][11][12][13][14][15][16] min; p < 0.0001) and an emergency procedure (68 [51-85] vs. 47 [37-57] min; p < 0.0001) were both shorter in the hybrid ER group. A significant association was found between the hybrid ER and decreased mortality (adjusted odds ratio [aOR], 0.50; 95% confidence interval [CI], 0.29-0.85; p = 0.011) and reduced deaths from exsanguination (aOR, 0.17; 95% CI, 0.06-0.47; p = 0.001).…”
Section: Clinical Experience With Severe Trauma In the Hybrid Ermentioning
confidence: 98%
“…A significant association was found between the hybrid ER and decreased mortality (adjusted odds ratio [aOR], 0.50; 95% confidence interval [CI], 0.29-0.85; p = 0.011) and reduced deaths from exsanguination (aOR, 0.17; 95% CI, 0.06-0.47; p = 0.001). The times to initiation of CT and emergency bleeding control procedures were also both shorter in the hybrid ER group versus the Conventional group (11 [8-16] vs. 26 [21][22][23][24][25][26][27][28][29][30][31][32] The first retrospective observational study on blood transfusion amounts during resuscitation in the hybrid ER was reported by Watanabe et al The amount of blood transfused was significantly lower in the hybrid ER versus nonhybrid ER group (whole blood: 8 vs. 14 units, p = 0.004; red blood cells: 2 vs. 6 units, p = 0.012; fresh frozen plasma: 6 vs. 9 units, p = 0.021). 29 This difference remained after propensity score matching (whole blood: 6 [4-16.5] vs. 28 units, p = 0.015; red blood cells: 2 [0-8.5] vs. 8 [2.75-26.5] units, p = 0.020; fresh frozen plasma: 6 [3.5-7.5] vs. 18 [5.5-27] units, p = 0.057).…”
Section: Clinical Experience With Severe Trauma In the Hybrid Ermentioning
confidence: 99%
See 1 more Smart Citation
“…The median patient age was 75 (69-83) years. The median GCS score on admission was 13 (10)(11)(12)(13)(14), the median NIHSS score was 15 (10-21), and the median ASPECTS score was 9 (6-10). In most patients, the culprit vessel was the middle cerebral artery (18/27).…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…Recently, the effectiveness of endovascular therapy has been proven in patients with large vascular occlusions in both the anterior and posterior circulation [1][2][3][4][5][6][7]. Although the eligible time window for DOI: https://doi.org/10.26676/jevtm.264 stroke [12]. Immediate endovascular therapy following CT evaluation can be performed without transfer to other rooms, which may contribute to improving the outcome in patients with ischemic stroke.…”
Section: Introductionmentioning
confidence: 99%